Radiation therapy for skin cancer - Mendenhall, William M.; Cognetta Jr., Armand B. (Springer New York, 2013)
Superficial radiation has been utilized by dermatologists for skin cancer and inflammatory diseases since the early 1900s.  This textbook is the progeny of multiple previous editors from 1926 on dedicated to its safe and effective usage of radiation therapy.  The rapid advancements in the field of Radiation Oncology, including electron beam therapy and tomotherapy, alongside the introduction of corticosteroids for dermatologic disorders and advancement in cutaneous surgery, have until recently eclipsed the utilization of this safe and effective modality.  Dermatologists look to our Radiation Oncology colleagues for help with many complex cancer scenarios, such as deeply invasive head and neck squamous cell carcinomas with or without perineural invasion, Merkel Cell Carcinoma, various sarcomas, and certain melanomas ranging from lentigo maligna to metastatic melanoma.  This textbook has a greatly expanded section that will serve as a vital reference for all cutaneous oncologists.